INFLUENCE OF INVESTMENT PROCESSES ON REGIONAL ECONOMIC DEVELOPMENT IN THE REPUBLIC OF KARAKALPAKSTAN - Sarsenbayev, Salauat Mukhammedovich (THE INNOVATION ECONOMY, 2026)
The article provides a comprehensive analysis of the impact of investment processes on regional economic development in the Republic of Karakalpakstan. The volume and structure of fixed capital investments and their influence on economic growth were assessed using statistical and analytical methods. Scientific recommendations aimed at enhancing regional investment activity are proposed.